Analysis of the unbalanced harmonic propagation in a three-phase power system using a parallel program. (August 2019) - Yunus, S; Dinata, U G S; Nazir, R; Aulia,
Abstract: Operation of non-linear in an unbalance condition can cause harmonic problems in the power system. There are two parts in the use of computing time in harmonic load flow, the first in the construction of harmonic admittance matrix and the second is the iteration scheme for solving systems of linear equations. The solution technique of the harmonic admittance was developed as a parallel application, and a direct algorithm to calculate the admittance matrix elements. The three-phase power flow program is devided into three independent subproblems, namely: positive, negative, and zero sequence network. Positive sequence network had been been solved by using the Newton Raphson method without modifying their formulation. Negative and zero sequence networks had been solved using nodal voltage equation. All three sequence networks have been modeled by three independent circuits and solved simultaneously using multi-core processors in parallel programming. The results showed that the parallel three-phase load flow speed is higher than the sequential.